A proposed paradigm for smart learning environment based on semantic web - Ouf, Shimaa; Abd Ellatif, Mahmoud; Salama, S.E.; Helmy, Yehia (Computers in human behavior, 2017)
The current approaches of e-learning face challenges, in isolation of learners from learning process, and shortage of learning process quality. The researchers mentioned that the next generation of e-learning is e-learning ecosystem. E-learning ecosystem has many advantages, in which, learners form groups, collaborate with each other and with educators, and content designed for interaction. E-learning ecosystem faces some issues. It applies teacher-student model, in which, fixed learning pathway is considered suitable for all learners. Consequently, learners are presented with limited personalized materials. E-learning ecosystem needs to merge the personalization's concept. Semantic web ontology based personalization of learning environment plays a leading role to build smart e-learning ecosystem. This paper previews a detailed study which addresses research papers that apply ontology within learning environment. Most of these studies focus on personalizing e-learning by providing learners with suitable learning objects, ignoring the other learning process components. This paper proposes and implements framework for smart e-learning ecosystem using ontology and SWRL. A new direction is proposed. This direction fosters the creation of a separate four ontologies for the personalized full learning package which is composed of learner model and all the learning process components (learning objects, learning activities and teaching methods). •A new direction for personalizing the learning environment is introduced.•This direction fosters the creation of a separate four ontologies.•A proposed paradigm which assures a smart and effective learning environment.